2022
DOI: 10.3390/molecules27061909
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Free Halodediazoniation of Arenediazonium Tetrafluoroborates in Deep Eutectic Solvents-like Mixtures

Abstract: Deep Eutectic Solvent (DES)-like mixtures, based on glycerol and different halide organic and inorganic salts, are successfully exploited as new media in copper-free halodediazoniation of arenediazonium salts. The reactions are carried out in absence of metal-based catalysts, at room temperature and in a short time. Pure target products are obtained without the need for chromatographic separation. The solvents are fully characterized, and a computational study is presented aiming to understand the reaction mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…It has been reported that these mechanisms prevail when arenediazonium salts are used as electrophilic reagents in Cu( i )-assisted nucleophilic substitution but cannot be ruled out with other leaving groups. 46 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that these mechanisms prevail when arenediazonium salts are used as electrophilic reagents in Cu( i )-assisted nucleophilic substitution but cannot be ruled out with other leaving groups. 46 …”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that these mechanisms prevail when arenediazonium salts are used as electrophilic reagents in Cu(I)-assisted nucleophilic substitution, but cannot be ruled out with other leaving groups. 46 To test the versatility of the methodology, Pd@CALB4 was evaluated in the C-H activation of 1 using iodobenzene (4) at 60ºC in methanol without additional base (Figure 5). A conversion of 52% was obtained after 24 h incubation, with a TOF value of 0.75 h -1.…”
Section: Catalytic Efficiency Of the Different Pd-hybrids In C-h Acti...mentioning
confidence: 99%
“…On these basis, we decided, in the light our previous researches, 13 to use DES as privileged solvent. Obviously, we have to choose a DES without halide salts as hydrogen bond acceptor to avoid Sandmeyer reactions.…”
Section: Resultsmentioning
confidence: 99%
“…We decide to explore the reactivity of benzyl chloride 4 with n -BuLi in different DESs ( Table 2 ), including the eutectic mixture Gly:KF 6:1 ( Table 2 , entry 4), recently designed and exploited by some of us [ 44 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%